Assessment of health risk perception and hygiene practice among waste collectors at selected local council / Siti Rohana Mohd Yatim ... [et al.] - Mohd Yatim, Siti Rohana; Ramli, Noor Ainor; Ku Hamid, Ku Halim; Noor Ismail, Kamariah; Abdul Rashid, Zulkifli; Zaki, Muhammad Afiq (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
A study on health risk perceptions among household waste collectors of municipal council was conducted to assess their perceptions on environmental, health and safety, to identify the symptoms that workers experienced and to identify the association of health symptoms with working environment. A survey questionnaire which specific to the environmental, health and safety components perception and health symptoms experienced was used in this study. The target population of this study were household waste collectors working in municipal council (n=100). The results revealed that the workers was satisfied with their working environment while the highest unsatisfactory perception was on exposure to unpleasant odour. As for hygiene practices, washing hand with antiseptic indicated significant association for cough, sore throat, nausea and boils. Then, there was association between health symptoms and eating at workplace for phlegm, sore throat, dizziness, nausea, vomiting, abdominal pain, stye and cellulitis. Overall findings of the study suggest that generally the household waste collectors had a positive and satisfactory response towards their working environment.